A review of some characters used in the taxonomy of Cryptops (subgenus Cryptops) (Chilopoda: Scolopendromorpha: Cryptopidae) - John G. E. Lewis (Soil Organisms, 2009)
Variation in a number of taxonomic characters in Cryptops (Cryptops) is discussed. Some, such as the shape of the poison gland calyx and the arrangement of setae on the anterior margin of the forcipular coxosternum, are very reliable. Others, such as the sutures of the head plate and tergite 1, although sometimes variable, are important, whereas others, for example the shape of sternite 21, are consistent for some species but not for others. Yet other characters are of little or no value. The fact that characters may change with age must be borne in mind. The importance of accurate illustration is stressed.